Global approaches to cocoa germplasm utilization and conservation: Final report of the CFC/ICCO/IPGRI project on ”Cocoa Germplasm Utilization and Conservation: a Global Approach” (1998-2004) - Eskes, A.B.; Efron, Y.; International Cocoa Organization; International Plant Genetic Resources Institute (2006)
Cocoa is a commodity produced in the developing countries of the tropics and consumed mostly in the middle- and high-income countries of the world's temperate zones. Currently, over 50 countries engage in cocoa production, of which some heavily rely on cocoa exports for their economic development as they contribute significantly to their foreign exchange earnings. From a level of 1.5 million tonnes in 1983-84, world production of cocoa beans is steadily rising and has reached a peak of 3.5 million tonnes in 2003-04. This significant increase is almost entirely due to an expansion of production area. Over 90% of world cocoa is produced by smallholder farmers who rely almost entirely on the supply of improved planting material from national and international research institutes. Nearly all producing countries grow cocoa on an extensive basis resulting in low average yields, which - on global average - have only increased little over the past three decades. This contrasts with the often dramatic advances in yields of other tropical or temperate crops and in particular for other raw materials, often used to manufacture snack foods which are competitive with cocoa. Gains in global yield and productivity of cocoa are now essential. As pressure on available land increases, the need for higher yielding, pest- and disease-resistant cocoa varieties becomes ever more urgent. This Technical Paper is the result of work undertaken in the CFC/ICCO/IPGRI project: ”Cocoa Germplasm Utilization and Conservation: a Global Approach”, which aimed at a more sustainable production of cocoa at lower costs, by making optimal use of cocoa germplasm. Special attention was paid to the evaluation and selection of resistance to some of the major diseases and pests, such as black pod, witches' broom, vascular streak dieback, moniliasis, cocoa swollen shoot virus and mirids, which together cause losses of an estimated 40% percent of annual world cocoa production. The Common Fund for Commodities acknowledges the significant inputs of both the International Cocoa Organization (ICCO) as Project Supervisory Body, and the International Plant Genetic Resources Institute (IPGRI) as Project Executing Agency for the successful implementation of the project in 12 countries. In line with the policy to disseminate the information produced by activities financed by the Fund, it is my expectation that this publication will be instrumental to make the results and experiences of this project available to a wider audience. It is hoped that extension workers, researchers and policy-makers would find this publication useful and relevant for improving access of higher yielding, good bean quality and disease-resistant cocoa varieties to farmers.